Application of AIMS65 Score in the Prediction of Clinical Outcomes of Patients with Upper Gastrointestinal Hemorrhage - Arunchai Chang (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND| 2020 Background: The AIMS65 score has been recognized as an accurate tool in predicting outcomes in patients with upper gastrointestinal hemorrhage (UGIH). Objective: To determine whether outcomes for patients presenting with UGIH differ depending on low-risk (AIMS65 <2) and high-risk (AIMS65 >2) scores. Materials and Methods: The authors conducted a retrospective comparison of in-hospital mortality, other clinical outcomes, and resource use between low-risk and high-risk UGIH patients in Hatyai Hospital between 2016 and 2017. Results: There were 322 patients with UGIH included in the present study, of whom 186 patients (57.8%) were low-risk and 136 patients (42.2%) were high-risk. When compared to low-risk patients, high-risk patients had increased risk of in-hospital mortality (11.8% vs. 2.7%, p = 0.001; adjusted hazard ratio (HR) 4.04, 95% confidence interval (CI) 1.34 to 12.16), needed blood transfusion (74.3% vs. 39.8%, p<0.001; adjusted HR 4.23, 95% CI 2.42 to 7.42), endoscopic intervention (44.1% vs. 24.7%, p<0.001; adjusted HR 2.06, 95% CI 1.19 to 3.57) and overall intervention (46.3% vs. 24.7%, p<0.001; adjusted HR 2.19, 95% CI 1.24 to 3.86). There was no significant difference in rebleeding between the two groups (3.7% vs. 2.2%, p = 0.501; adjusted HR 1.71, 95% CI 0.43 to 6.87). High-risk patients were associated with longer hospitalization (median (IQR) = 5 (4 to 7) days vs. 4 (3 to 5) days, p<0.001) and higher hospitalization cost (median (IQR) = 687.4 (450.7 to 1,023.1) vs. 537.1 (388.5 to 819.1) US dollars, p<0.001). Conclusion: The AIMS65 score is simple and accurate in predicting clinical outcomes. High-risk patients (AIMS65 >2) had increased risk of in-hospital mortality and needed of blood transfusion, endoscopic intervention, and overall intervention and were associated with greater hospital stay and cost.